2017
DOI: 10.1186/s12879-017-2697-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of hepatitis B virus in Vietnam

Abstract: Background: Hepatitis B virus (HBV) infection is a major public health problem globally. HBV genotypes and subgenotypes influence disease transmission, progression, and treatment outcome. A study was conducted among treatment naive chronic HBV patients in southern Vietnam to determine the genotypes and subgenotypes of HBV. Methods: A prospective, exploratory study was conducted among treatment naïve chronic HBV patients attending at the Hospital for Tropical Diseases, in Ho Chi Minh City, Vietnam during 2012, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 26 publications
6
29
0
Order By: Relevance
“…31 Our result was similar to previous studies conducted in Vietnam that indicated that HBV genotype B was the most prevalent (63.0%-72.6%) followed by genotype C (18.0%-28.0%). [32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group.…”
Section: Discussionsupporting
confidence: 62%
“…31 Our result was similar to previous studies conducted in Vietnam that indicated that HBV genotype B was the most prevalent (63.0%-72.6%) followed by genotype C (18.0%-28.0%). [32][33][34][35] Like other studies, 5,6,23,24,28,36 our results also showed no statistically significant association between possible occupational risk factors for HBV infection among beauticians. However, some studies have suggested that beauticians are a high-risk group for HBV and HCV infections based on the statistically significant difference in prevalence among case and control groups, 24,36,37 or by comparing HBV infected cases with HAV infected cases as a control group.…”
Section: Discussionsupporting
confidence: 62%
“…Based on the EcoRI numbering convention, breakages tend to occur at sites within nucleotides 1700–2000 and 2100–2300, 83 possibly because of the decreased between-genotype diversity observed in these regions. In addition to the genotype I recombinant, examples include B and C recombinants in parts of mainland East Asia that are now defined as sub-genotypes B2, 22 , 84 B3, 85 and B4 85 ; C and D recombinants reported from Tibet 83 and China84, 86; D and E recombinants reported from different parts of Africa87, 88; A, C, and G recombinants reported in 2 patients in China—although this is based on sequencing only a 1-kb stretch of the genome 89 ; and A and G recombinant sequences identified in a patient with A2 infection 90 and in several patients in Canada 91 …”
Section: Recombinationmentioning
confidence: 99%
“…HBV sequence data largely consist of consensus sequences of individual viral genes derived by Sanger sequencing. However, next-generation sequencing (NGS) platforms are rapidly becoming more accessible and affordable, in addition to new bioinformatic approaches to handle the resulting datasets 21, 22, 23. In addition to enabling whole-genome sequencing, NGS offers a powerful method for detection of minor variants relevant to the identification of drug resistance,24, 25, 26 studies of quasispecies dynamics, 27 and characterization of complex viral populations 28 .…”
mentioning
confidence: 99%
“…The genome sequences revealed the genotype distribution pattern of HBV in the whole Cambodia. where HBV genotype B is predominant (72.6%); particularly sub-genotype B4 (87.8%) [27]. HBV genotype C was abundantly found in the Stung Treng, Ratanakiri and Preah Vihear provinces, the northeast part of Cambodia and border region to Laos, where HBV genotype C (55.4%) is also predominant [28].…”
Section: Discussionmentioning
confidence: 99%